Use of sEMG for Swallowing Muscles Activity Quantification in Acute Phase of Stroke - Biben, Vitriana; Tanuwijaya, Andre; Wardhani, Ildzamar Haifa; Amalia, Lisda (Faculty of Medicine, Universitas Padjadjaran, 2023)
Early diagnosis of dysphagia and aspiration risk is very important in minimizing the risk of various medical consequences. This study aimed to establish a scientific database for future sEMG-based dysphagia screening investigations by examining the electrical activity of swallowing muscles in acute stroke cases. A quantitative cross-sectional study was conducted on 61 stroke inpatients admitted to Dr. Hasan Sadikin General Hospital, Bandung, Indonesia, from July to November 2019. The objective of this study was to quantify electrical activities of the suprahyoid (SH) and infrahyoid (IH) muscles during swallowing. Patients participated in both dry swallowing and a 3 mL water swallowing task, with the sEMG used to measure electrical activity parameters (duration, swallowing initiation, time-to-peak, and amplitude) on both paretic and normal sides. The Wilcoxon test was used to compare the electrical activity parameters between the patients paretic and normal sides. Only amplitude showed a significant difference between the paretic and normal side (p=0.023) when performing the 3 mL water swallowing test. Other parameters did not exhibit significant differences in activity between muscle groups during both swallowing tests (p>0.05), although varying water volumes led to distinct activities in both muscles. Despite the absence of a clear pattern in SH and IH contractions during swallowing, the result showed that the sEMG quantification method might become a promising method for screening dysphagia, complementary to FEES and VFSS. The non-invasive and cost-effective sEMG method can serve as an early screening tool for dysphagia in stroke patients. This study underscores the importance of further investigation on sEMG use, incorporating a larger sample size and diverse cohort results with various swallowing exercises (varying in volume and viscosity) to validate the use of sEMG in dysphagia screening.